2020
DOI: 10.3389/fpsyg.2020.00664
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and [Possible] Solutions to Optimizing Talent Identification and Development in Sport

Abstract: The modern-day landscape of Olympic and Professional sport is arguably more competitive than ever. One consequence of this is the increased focus on identifying and developing early athletic talent. In this paper, we highlight key challenges associated with talent (athlete) identification and development and propose possible solutions that could be considered by research and practice. The first challenge focuses on clarifying the purposes of talent identification initiatives such as defining what talent is and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
146
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(179 citation statements)
references
References 105 publications
1
146
0
3
Order By: Relevance
“…A collaborative relationship between organizational and environmental factors (e.g., school—club communication) [ 46 ] and appropriate social support (especially family support) can help to prevent elite athletes’ premature career termination during and after their normative transition, within the transition from junior to senior level. As a result, it is important to educate parents, coaches, and teammates on the different roles they can play in providing the necessary social support to athletes undergoing normative within-career transitions [ 22 , 45 , 47 ]. Successful interventions should be based on assessment of athletes’ needs and on context-specific recommendations about what works and what does not work in helping athletes in different developmental stages (e.g., junior vs. senior) [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A collaborative relationship between organizational and environmental factors (e.g., school—club communication) [ 46 ] and appropriate social support (especially family support) can help to prevent elite athletes’ premature career termination during and after their normative transition, within the transition from junior to senior level. As a result, it is important to educate parents, coaches, and teammates on the different roles they can play in providing the necessary social support to athletes undergoing normative within-career transitions [ 22 , 45 , 47 ]. Successful interventions should be based on assessment of athletes’ needs and on context-specific recommendations about what works and what does not work in helping athletes in different developmental stages (e.g., junior vs. senior) [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the study was retrospective in character, and the respondents’ answers may have been influenced by time. However, retrospective research designs are suggested to monitor the characteristics of young athletes aligned to future success [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The international arena of track and field has become so popular and competitive that governing bodies do their best to achieve success on the international stage to at least some of their junior talented athletes. 1,2 Numerous talent identification programs aimed at selecting and developing sports talent have been proposed over recent years. [3][4][5][6] While it is clear that talent is multidimensional in nature, a comprehensive and accepted definition of sports talent is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] While it is clear that talent is multidimensional in nature, a comprehensive and accepted definition of sports talent is lacking. 2,7,8 However, many authors agree that talent in sports relates to the presence of particular skills at an early age that predicts future performance. 7,9 Consequently, a talented athlete is an individual whose athletic performances are superior to his/ her peer group at any given time and has the potential to reach elite-level performances in adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…However, the validity of coach decisions during talent identification is extremely difficult to determine due to the prognostic nature of these decisions, and the inherent de-selections that occur as part of the talent identification process. Without a formal assessment of coach accuracy and reliability, evaluating success or measuring talent identification methods over time will always be limited (Till and Baker, 2020 ). Despite anecdotal discussions, a fundamental unanswered question is; If viewed in the same context, would multiple coaches deem the same athlete(s) as “talented” and “untalented” when assessing their future potential?…”
Section: Introductionmentioning
confidence: 99%